the absolute value of the product of the zeros of a is [tex]-108[/tex] .
Step-by-step explanation:
Here we have , [tex]a(t) = (t - k)(t - 3)(t - 6)(t + 3)[/tex] is a polynomial function of t, where k is a constant. Given that a(2) = 0 . We need to find the absolute value of the product of the zeros of a . Let's find out:
Equation every factor of a(t) to zero we get:
⇒ [tex]a(t) = (t - k)(t - 3)(t - 6)(t + 3) = 0[/tex]
⇒ [tex](t - k) =0\\(t - 3)=0\\(t - 6)=0\\(t + 3) = 0[/tex]
⇒ [tex]t =k\\t =3\\t = 6\\t =- 3[/tex]
But , t=2 So , [tex]k=2[/tex] . Now , the absolute value of the product of the zeros of a is :
⇒ [tex]k(3)(6)(-3)[/tex]
⇒ [tex]2(3)(6)(-3)[/tex]
⇒ [tex]-108[/tex]
Therefore, the absolute value of the product of the zeros of a is [tex]-108[/tex] .